Drainage Network System of Sekaran Village, Gunungpati District, Semarang City - Utomo, Karuniadi Satrijo; Sutopo, Yeri; Adi, Muhammad Hamas (Universitas Negeri Semarang, 2019)
Abstract. Drainage functions to drain, deplete, remove or transport water. Generally, drainage is defined as a series of water facility used to reduce and/or remove excess water from an area or land, so that the land can be functioned optimally. Drainage is also realized as an effort to control the quality of groundwater in relation to salinity. The case study was carried on in Sekaran Village, Gunungpati District, Semarang City. The area size of Sekaran Village is 6,21 km². According to the writing method, the author used tools and materials required in this research. The tools used were a roll meter and Arcmap software as a medium for data-processing, and the materials taken was data regarding information about the condition of Sekaran Village in the extent of topographic maps, rainfall data. The method of data calculation used manual calculations in accordance with the rational method to figure out the rain discharge, and the manning formula for channel flowrate. The numbers of design rainfall for 5 years and 10 years was 169,365 mm and 171,502 mm; while the design discharge with return period of 5 and 10 years, for example, in channel 1 was branch 1 was of 0,6772 m³/s and the main channel was 5,7910 m³/s; The economic channel dimensions for the main channels 1 and 4 were the base width B = 1,596 m ≈ 1.6 m and the water height h = 0,796 m ≈ 8 0,8 m, the cross section was square.